Description Quality of Sleep of Children With Autism - Dewi Umu Kulsum; Oktavia Oktavia (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: A developmental disorder that affects communication and behavior is known as Autism. The prevalence of autism is still increasing, ranging from 1-2/1000 in males more than in females (4:1). In children with autism, physical health problems are often complained of, one of which is sleep problems, such as delayed sleep onset, frequent awakenings at night, and sleep duration. This problem makes parents stressed because it impacts the severity of behavior both during the day and at night. Objectives: The description of sleep quality in children with autism. Methods: Cross-sectional approach to 55 special school students with autism in Cimahi. Data collection was collected by measuring sleep quality with the Children's Sleep Habits Questionnaire (CSHQ) with a cut-off point of < 30 good sleep quality and > 30 sleep problems with Chronbach's alpha = 0.68 to 0.78. Content validity; ROC = 0.41, differentiating between clinical and control groups; sensitivity = 0.80, specificity = 0.72. Data analysis was carried out univariate (frequency distribution) and bivariate with a chi-square test. Results: It was found that most of the children with moderate Autism had sleep problems (54.5%) p = 0.005. Conclusion: The study results describe that some children with autism in the city of Cimahi have sleep problems in conditions of delayed sleep onset and often wake up at night.